Assessment of factors associated with diabetic retinopathy among diabetic patients in Zambia - Kabaso, Kanasa (Department of Public Health and Family Medicine, 2019)
Background: Diabetes Mellitus is an emerging public health problem in Africa. Evidence suggests that globalization, rapid urbanization and a nutritional transition have led to the rise in the prevalence of diabetes mellitus in Africa. Diabetic retinopathy is a common complication of diabetes mellitus that causes visual impairment and subsequent blindness. Early detection and prompt treatment can prevent blindness in up to 90% of patients. The common risk factors for diabetic retinopathy include hypertension, hyperglycemia and long duration of diabetes. Other risk factors include obesity, hyperlipidemia, smoking, puberty and pregnancy. There is limited data on diabetic retinopathy and its associated risk factors in Zambia. An understanding of these factors would help in the effective management of diabetic retinopathy. Methods: A secondary data analysis of data obtained from a hospital-based cross-sectional study of diabetic patients attending diabetic clinics in the Copperbelt Province in Zambia was carried out. All diabetic patients that attended the retinopathy-screening program between April 2012 and September 2012 were eligible for the primary study. The secondary data analysis was restricted to patients 18 years and older. Data analysis was carried out by R version 3.3.1. The characteristics of the study population were summarized using descriptive statistics. Univariate logistic regression analysis was used to select potential candidates for the multivariate regression model at p-value cutoff point ≤ 0.25 and variables of known clinical relevance were also included in the multivariable analysis. The final model fitness was checked using Hosmer and Lemeshow chi-square test. Finally, statistical significance was tested at P-value <0.05. Results: The prevalence of diabetic retinopathy was 19.4%. Multivariate analysis showed that the odds of diabetic retinopathy were significantly associated with age (OR =1.05: 95%Cl; 1.03-1.06), duration (OR=1.39: 95%Cl; 1.27-1.52), weight (OR =0.98: 95%Cl; 0.97-0.98), blood glucose (OR =1.04: 95Cl; 1.02-1.07) and systolic blood pressure (OR = 1.01: 95Cl; 1.00-1.02). Conclusion: Duration of diabetes, age, systolic blood pressure, weight and blood glucose levels were significantly associated with diabetic retinopathy in this study. More comprehensive population screening strategies and treatment programs addressing these risk factors should be put in place.